Improving system performance through operating system optimization on embedded devices platform - Daud, S.; Khalib, Z.I.A.; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org